Advanced Ambiance Sensing Device using ESP32 and BME680 (International Journal of Scientific Research in Science and Technology, 2024)
Occupational structure is the distribution or division of working population in different sectors based on occupations. It is one of the key elements in manifestation of population composition of a region. The economy is segregated based on its occupational structure namely, the agriculture sector, industrial or manufacturing sector and service sector. Occupational structure provides clear picture of working and non-working population in an area. The growth and prosperity of a region largely depends on the size of working population and proportion of productive workers engaged in various economic activities. The objective of this study is to find out the shift in occupation from primary sector to other sectors and the rate of change in last two decades from 2001 to 2011 in Kerala state with district as spatial unit. The study is based upon the secondary data collected from Census 2001 and 2011.By using GIS techniques thematic maps were prepared to show the variation in occupational structure in the study area. To find out the changes in occupational structure, percentage of workers engaged in four categories are to be calculated. There is a remarkable shift of workers from agriculture to non-agricultural sector in Kerala.